Does trade increase total factor productivity: cointegration evidence for Chile - Dierk Herzer (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
In this study, we examine the long-run impact of capital goods imports, exports of manufactured and primary goods on total factor productivity in Chile. Using the integration and cointegration techniques of Kapetanios (2005), Pesaran, Shin, and Smith (2001), Stock (1987), and Saikkonen (1991) we find a long-run relationship between these variables. All in all, our estimation results provide evidence for the existence of productivity-enhancing effects of capital goods imports and manufactured exports and of productivity-limiting effects of primary exports.
Keywords: O47; F41; C22; 330; Trade; trade composition; productivity; cointegration